Community-organised disaster response to the 2019 Northeast Brazil Oil Spill in small-scale fishing territories in Bahia, Brazil - Sentilles, Frances; Machado, Louise O. R.; Rêgo, Rita de Cássia Franco (Sustainability in Debate, 2025)
The 2019 Northeast Brazil Oil Spill represents an opportunity to observe small-scale fishing communities’ disaster response capacity and identify opportunities to improve resilience. With a delayed and disjointed national government response, many communities organised clean-up activities and other actions. A mixed-methods study including a questionnaire (n=168) and semi-structured interviews (n=11) was conducted in two municipalities in Bahia to analyse the disaster response. 66.1% (111/168) of the questionnaire respondents participated in clean-up efforts, with greater participation in the community, with more fishing trade associations and government support. The rapid mobilisation of these volunteer efforts was a positive indicator of resilience, although fishers’ involvement puts them at risk for health consequences. Risk management, access to materials, and emergency literacy were weaknesses in the disaster response. While government management and ownership are needed during acute disasters, partnerships with fishing communities could serve to enhance disaster resilience due to their pre-existing organisational structures and demonstrated willingness to volunteer as first responders.